DEMYSTIFYING THE MYTH OF COSMOPOLITANISM: ARE WE TRULY LIVING IN A BORDERLESS WORLD? - Aspin Nur Arifin Rivai; Gema Ramadhan Bastari (UIN ALAUDDIN MAKASSAR, 2019)
This paper will discuss about the possibility that cosmopolitanism as an idea might only exist as a myth. It begins by questioning the hypocrisy surrounding our everyday life where powerful countries preach about living in dignity but ended up taking away that very dignity itself. If cosmopolitanism is defined as an idea that give worth to every human being, no matter their affiliation, then the current state of the world does not reflect that idea at all. This paper will attempt to demystify the practice of cosmopolitanism in modern era. This paper then found that cosmopolitanism is basically a political project for the powerful to inject their idea into weaker actor, in order to create hegemony. Whether someone’s act can be considered cosmopolitan or not depends on their capability to exercise their power. In the end, this paper concludes that cosmopolitanism as a standard of morality does not exist in our world. A borderless world might exist, but it is up to the powerful to decide who can live in it. For most people, cosmopolitanism remains a myth that could never bring salvation. Kata kunci: Cosmopolitanism, Morality, Hegemony.